2017
DOI: 10.1108/caer-04-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

Risk aversion in crop insurance program purchase decisions

Abstract: Purpose The purpose of this paper is to contribute to the aforementioned literature on the linkage between economic activity and human preference by estimating the cross-sectional determinants of farmers’ participation in participation in crop insurance programs (CIPs) and identifying the impediments preventing the remaining farmers from participating. Design/methodology/approach Using the unique data sets of risk preference experiments and maize producer surveys pertaining to the maize production areas of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
2
14
1
1
Order By: Relevance
“…This ambiguity has been discussed by Peng and Pang (2019), who found that farmers' risk aversion increased with the farm size. In contrast with our research finding, Lyu and Barré (2017); Belissa et al (2019) and Yanuarti et al (2019) have found that farmer's risk aversion level had a significant influence towards their decision to participate in insurance. Farmers with high risk aversion would be willing to join agricultural insurance.…”
Section: Resultscontrasting
confidence: 99%
“…This ambiguity has been discussed by Peng and Pang (2019), who found that farmers' risk aversion increased with the farm size. In contrast with our research finding, Lyu and Barré (2017); Belissa et al (2019) and Yanuarti et al (2019) have found that farmer's risk aversion level had a significant influence towards their decision to participate in insurance. Farmers with high risk aversion would be willing to join agricultural insurance.…”
Section: Resultscontrasting
confidence: 99%
“…These results are consistent with Lyu and Barré (2017) research which states that farmers with high risk aversion and large planting areas will be willing to participate in agricultural insurance. Conversely, farmers with low risk aversion and small cropland areas will refuse to participate.…”
Section: Risk Aversion Levelsupporting
confidence: 91%
“…Farmers with a high perception of risk generally take part in an insurance program. Lyu and Barré (2017) analyse farmer risk aversion levels by using a ball-game experiment. The experimental design was modified so it would easily be understood by farmers.…”
mentioning
confidence: 99%
“…Based on logistic regression result of RAL variable, we can conclude that the result was consistent with a previous study [10] which stated that farmers with high risk aversion and large planting areas would be willing to participate in agricultural insurance. Conversely farmers with low risk aversion and small land areas will refuse to participate, or in other words, Farmers who do not like risk will tend to participate in insurance.…”
Section: Resultssupporting
confidence: 90%
“…The focus of agricultural insurance research in Indonesia mainly about agricultural insurance models that suitable to be applied in Indonesia, for example feasibility and perspective of developing rice and corn insurance [7] [8], and specifically climate insurance models, which was still focused on the design of agricultural insurance models in Indonesia [9]. Research that addresses the existence of adverse selection in the implementation of agricultural insurance has been carried out in China [10] [11]. Adverse selection affects the farmer's decision to take insurance.…”
Section: Introductionmentioning
confidence: 99%